Slavery in the Great Lakes Region of East Africa - Médard, Henri; Doyle, Shane (Shane Declan) (Eastern African studies (London, England), 2016)
"Slavery in the Great Lakes Region of East Africa looks at the perceptions of one of the main themes of African history: slavery. There was no single form of slavery, and the line between enslaved and nonslave labor was fine. This book challenges the assertion that domestic slavery increased in Africa as the result of the international trade."--Provided by publisher.